Independent control of multiple magnetic microrobots in three dimensions. (April 2013) - Diller, Eric; Giltinan, Joshua; Sitti, Metin
A major challenge for untethered microscale mobile robotics is the control of many agents in the same workspace for distributed operation. In this work, we present a new method to independently control multiple sub-mm microrobots in three dimensions (3D) using magnetic gradient pulling as the 3D motion generation method. Motion differentiation is accomplished through the use of geometrically or magnetically distinct microrobots which assume different magnetization directions in a rotating or oscillating magnetic field. This allows for different magnetic forces to be exerted on each, enabling independent motion control and path following of multiple microrobots along arbitrary 3D trajectories. Path following in 3D with less than 310 μ m mean error is shown for a set of two microrobots of size 350 μ m and 1500 μ m, and independent motions are shown with three microrobots. It is also shown that control of more microrobots could be possible using improved magnetic coil hardware. Microrobot diversity is analyzed with regards to the effect on independent control. The proposed addressability method could be used for the 3D control of a team of microrobots inside microfluidic channels or in the human body for localized therapy or diagnostics.